2020
DOI: 10.3389/fpsyg.2020.572343
|View full text |Cite
|
Sign up to set email alerts
|

A Corporate Purpose as an Antecedent to Employee Motivation and Work Engagement

Abstract: It is generally assumed that a corporate purpose aiming to benefit all stakeholders has a positive effect on employee motivation and engagement, but no empirical studies into these specific effects were found. To examine this assumption, a corporate mission and vision matching the definition of a higher purpose were tested in two subsequent studies. The first study (N = 270) was a cross-sectional self-report study. The second study included a longitudinal design (N = 56) modeling purpose, motivation, and engag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 87 publications
6
49
0
5
Order By: Relevance
“…The interviews also indicated that purpose could lead to meaningful work and engagement at the individual level. In line with previous research (van Tuin et al, 2020;van Ingen et al, 2021), some interviewees addressed benefits such as commitment, fulfillment, happiness, loyalty, optimism, pride, satisfaction, trust, a sense of belonging, and well-being:…”
Section: Consequences Within Organizational Boundariesmentioning
confidence: 82%
See 1 more Smart Citation
“…The interviews also indicated that purpose could lead to meaningful work and engagement at the individual level. In line with previous research (van Tuin et al, 2020;van Ingen et al, 2021), some interviewees addressed benefits such as commitment, fulfillment, happiness, loyalty, optimism, pride, satisfaction, trust, a sense of belonging, and well-being:…”
Section: Consequences Within Organizational Boundariesmentioning
confidence: 82%
“…Operationalizations in the abovementioned perspectives are also limited. For example, organizational purpose is based on a professional and practical definition (van Ingen et al, 2021), or on items constructed from related though distinct constructs, such as meaningful work (Gartenberg et al, 2019), or on mission (i.e., what you want to achieve in terms of specific activities, specific goals, and a specific timeline), vision (i.e., an imagined future state of what it will be like when the purpose is being lived and the mission accomplished), and (shared) values (i.e., the way how you do business and not why) (van Tuin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Such a different approach would also pre-empt legitimacy concerns and invite organizations to engage in more spontaneous disclosure. When employees perceive that their organization strives for a positive impact out of a strong sense of purpose, this positively affects employees' psychological well-being [64] and work engagement [65]. Conversely, when the motivation of an organization to engage in CSR is perceived to be externally regulated, this can have downstream effects on employee motivation and engagement [66][67][68][69].…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…SWL has often been called life satisfaction, which is a judgmental process, wherein the person assesses quality of life based on his/her own criteria ( Vanhoutte and Nazroo, 2016 ). EWB or eudaimonic well-being includes acceptance and appreciation of oneself, or self-esteem, having positive relationships with other people, feeling capable of effectively working and acting, and that one is learning or undergoing personal growth, that includes a purpose in life and a feeling of personal psychological and social autonomy ( Suh and Koo, 2008 ; van Tuin et al, 2020 ). For its part, social well-being (SWB) refers to the extent to which one’s surroundings provide for a full life or facilitate realization of the most valuable human potential ( Ryan et al, 2008 ; Mackenzie et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%